A secure, fast insert and efficient search order preserving encryption scheme for outsourced databases. (17th May 2019) - Reddy, K. Srinivasa; Ramachandram, S.
Order preserving encryption (OPE) schemes have been studied to a great extent in the cryptography literature because of their potential application to database design. For the first time, a scheme called mutable order preserving encoding (mOPE) is introduced to achieve indistinguishability under ordered chosen plaintext attack (IND-OCPA) security. However, even mOPE scheme potentially leaks the distribution of repeated ciphertexts and is less efficient. In this paper, a new scheme is introduced called as a secure and cost efficient order preserving encryption (SCOPE), which is considerably more secure and efficient than mOPE scheme. A new form of strong security notion called as indistinguishability under ordered chosen repeated plaintext distribution attack (IND-OCRPDA) is proposed and we show that SCOPE scheme is IND-OCRPDA secure. Finally, the experimental results show that SCOPE achieves good performance in the context of an encrypted database and have a reasonable overhead which is 3.5× compared to plain data.